A review on experimental investigations of refrigerant/oil mixture flow boiling in horizontal channels. (September 2021) - Chu, Wenxiao; Yan, Gang; Zhang, Hao; Zhao, Fufeng; Wang, Qingxian; Wang, Qiuwang
Highlights: Experimental studies on refrigerant/oil mixtures flow boiling inside horizontal channels are summarized. Vital factors that affecting flow boiling behaviors are discussed based on flow channel scales. Correlations for predicting two-phase HTC and pressure drop with applicable ranges are summarized. Studies on heat transfer augmentation techniques by introducing microfins and metal foams are reviewed. Studies on comprehensive performance of refrigerant/oil mixture flow boiling with nanoparticles are reviewed. Abstract: The flow boiling process of refrigerants indicates significant influence on the refrigeration system performance. With the development of environmental standards in the last two decades, various refrigerants with low Global Warming Potential (GWP) and none ozone depletion potential (ODP). This study provides a review upon flow boiling behavior of refrigerants impacting by lubricant oil. Experimental studies on flow regimes of refrigerant/oil mixtures in macro-scale and that in mini- and micro-scale flow channels are respectively summarized in this review. Meanwhile, correlations with applicable ranges involving refrigerant mass velocities, heat fluxes, vapor mass qualities and oil concentrations are also examined and concluded for predicting the two-phase heat transfer coefficient (HTC) and pressure drop. For achieving better comprehensive thermal performance, experimental studies on augmentation structures with the application of microfin and metal-foam tubes are also reviewed. Moreover, the effect of nanoparticles on the flow boiling heat transfer is considered, which sometimes shows negative effect, but not always. This review aims to serve as a reference guide for experimental measurement of refrigerant flow boiling as far as the effect of lubricant oil is concerned. Moreover, some research efforts in the further studies as well as potential enhancement measures are also addressed.